Cuneiform Studies and the History of Civilization. Papers read April 19, 1963, in the Symposium on Cuneiform Studies and the History of Civilization (2000)
Die einzelnen Beiträge s. unter 26:d:618; 26:d:906; 26:d:1042; 26:d:1377; 26:d:1689.